Thematic Groups And Features Of National Geographic'S Vr-Content - Kyrylova, Oksana; Anatska, Hanna (Zenodo, 2018)
The article provides the research regarding the VR-content on National Geographic’s Youtube-channel within October 2016 - January 2018. The thematic groups of video-360о were distinguishes, with further studying its structure and features. The following videos were analyzed: «Glow Worm Caves of New Zealand», «Great Hammerhead Shark Encounter», «Antarctica - Unexpected Snow», «Kamchatka Volcano Eruption», «Dive Through an Oil Rig Ecosystem», «Swimming With Bears», «Victoria Falls – The Devil’s Pool», «Antarctica - Journey Through The Ice», «Victoria Falls - The Canyons Below», «Bryce Canyon», «Underwater National Park», «3D Monarch Butterflies», «Climbing Giants», «Giant Sequoias on a Changing Planet», «Viking Battle», «The Long Road Home», «Live from «Mars», «Genius», «Wingwalker». The research described and analyzed the thematic features and their structural peculiarities of the VR-content of the National Geographic YouTube channel. The method of observation is used to identify thematic groups and structural features. Using the comparative method, the structural features of various thematic groups of the video-360о National Geographic were outlined. The research results indicate that the VR content of the Youtube-channel can be categorized into thematic groups. It also shows that VR-content is becoming popular and the world media use it in various thematic aspects. Also the results indicate that National Geographic uses VR-content for advertising its own products. In the course of the study, five thematic video-360о groups were singled out: «Nature», «Man and Nature», «Person», «Event» and «Promo». The structure of the video and their features are considered. The results indicate that the National Geographic Youtube channel’s VR content has certain structural and thematic features. The research has practical implications for the subsequent study of VR-content development, since they can be used to further study both the National Geographic VR-content in particular and the VR content in a whole. : {"references": ["Kyrylova, \u041e. (2017), \"Immersive journalism: the experience of world news sources\", Visnyk Dnipropetrovs'kogho Universytetu. Serija \u00abSocialjni komunikaciji\u00bb [Dnipropetrovsk University Bulletin: Social Communications] [Visnyk Dnipropetrovs'koho universytetu. Seriya Sotsial'ni Komunikatsiyi], vol. 25, no 12, issue 17, pp. 51\u201357, available at: https://vesnik-fszmk.dp.ua/index.php/FSZMK/article/view/104 (accessed 28 November 2017).", "Youtube.com (2017), \"National Geographic\", available at: https://www.youtube.com/ channel/UCpVm7bg6pXKo1Pr6k5kxG9A (accessed 28 November 2017).", "NationalGeographic.com (2016), \"Introducing the First Virtual Reality Experience Featuring President Obama\", available at: http://press.nationalgeographic.com/2016/08/25/ introducing-the-first-virtual-reality-experience-featuring-president-obama (accessed 28 November 2017).", "Walkinginrangersshoes.com (2016), \"The Protectors\", available at: http://www.walkinginrangersshoes.com (accessed 28 November 2017).", "Synnott, M. (2017), \"The Last Death-Defying Honey Hunter of Nepal\", National Geographic, no 7, available at: https://www.nationalgeographic.com/magazine/2017/07/honey-hunters-bees-climbing-nepal (accessed 28 November 2017).", "White, M. (2016), \"Inside the Private Lives of Orangutans\", National Geographic, no 12, available at: https://www.nationalgeographic.com/magazine/2016/12/orangutans-behaviors-borneo-sumatra (accessed 28 November 2017).", "Pringle, H. (2017), \"What You Don't Know About the Vikings\", National Geographic, no 3, available at: https://www.nationalgeographic.com/magazine/2017/03/vikings-ship-burials-battle-reenactor (accessed 28 November 2017).", "NationalGeographic.com (2017), \"The Long Road Home\", available at: http://channel. nationalgeographic.com/the-long-road-home/ (accessed 28 November 2017).", "NationalGeographic.com (2016), \"Mars\", available at: http://channel.nationalgeographic. com/mars (accessed 28 November 2017).", "NationalGeographic.com (2017), \"Explore Life on \u00abMars\u00bb in Our 360\u00b0 Video Tour\", available at: https://news.nationalgeographic.com/2017/09/mars-national-geographic-channel-tv-show-tour-360-video (accessed 28 November 2017).", "NationalGeographic.com (2017), \"Genius\", available at: http://channel. nationalgeographic.com/genius (accessed 28 November 2017).", "Cope, S. (2017), \"The Last Wingwalker\", BuzzFeed, Jan 5, available at: https://www.buzzfeed.com/suzannecope/up-in-the-air-with-carol-pilon-americas-last-great-wingwalke?utm_term=.crn63Dbvq#.fy5JLd8jR (accessed 28 November 2017).", "De la Pe\u00f1a, N., Friedman, D., Llobera, J., Sanchez-Vives, M., Slater, M., Spanlang, B. and Weil, P. (2010), \"Immersive journalism: Immersive virtual reality for the first-person experience of news\", Presence: Teleoper. Virtual Environ, vol. 19, issue 4, p\u0440. 291\u2013301, available at: www.mitpressjournals.org/doi/abs/10.1162/PRES_a_00005."]}